From simple questions to complex issues, IDNLearn.com has the answers you need. Discover prompt and accurate answers from our community of experienced professionals.
Sagot :
To solve the equation [tex]\( x^2 + 2x = 1 \)[/tex] by completing the square, follow these steps:
1. Rewrite the equation in standard form:
[tex]\[ x^2 + 2x - 1 = 0 \][/tex]
2. Move the constant term to the right side:
[tex]\[ x^2 + 2x = 1 \][/tex]
3. Complete the square:
To complete the square, take the coefficient of [tex]\( x \)[/tex] (which is 2), divide it by 2, and then square the result:
[tex]\[ \left( \frac{2}{2} \right)^2 = 1 \][/tex]
Add and subtract this square inside the equation:
[tex]\[ x^2 + 2x + 1 - 1 = 1 \][/tex]
[tex]\[ x^2 + 2x + 1 = 2 \][/tex]
The left side can now be written as a perfect square:
[tex]\[ (x + 1)^2 = 2 \][/tex]
4. Take the square root of both sides:
[tex]\[ x + 1 = \pm \sqrt{2} \][/tex]
5. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \pm \sqrt{2} - 1 \][/tex]
Thus, the solutions from this method are:
[tex]\[ x = \sqrt{2} - 1 \quad \text{or} \quad x = -\sqrt{2} - 1 \][/tex]
Additionally, considering the standard quadratic roots and any additional solutions, we have:
[tex]\[ x = 2 \quad \text{and} \quad x = 0 \][/tex]
So, the complete set of solutions is:
[tex]\[ x = \sqrt{2} - 1, \quad x = -\sqrt{2} - 1, \quad x = \sqrt{2} + 1, \quad x = -\sqrt{2} + 1, \quad x = 2, \quad x = 0 \][/tex]
The numerical approximate values are:
[tex]\[ x \approx -2.414213562373095 \][/tex]
[tex]\[ x \approx 0.41421356237309515 \][/tex]
[tex]\[ x \approx -0.41421356237309515 \][/tex]
[tex]\[ x \approx 2.414213562373095 \][/tex]
[tex]\[ x = 2 \][/tex]
[tex]\[ x = 0 \][/tex]
Therefore, the approximate solutions to the equation [tex]\( x^2 + 2x = 1 \)[/tex] are:
[tex]\[ -2.414213562373095, \; 0.41421356237309515, \; -0.41421356237309515, \; 2.414213562373095, \; 2, \; 0 \][/tex]
1. Rewrite the equation in standard form:
[tex]\[ x^2 + 2x - 1 = 0 \][/tex]
2. Move the constant term to the right side:
[tex]\[ x^2 + 2x = 1 \][/tex]
3. Complete the square:
To complete the square, take the coefficient of [tex]\( x \)[/tex] (which is 2), divide it by 2, and then square the result:
[tex]\[ \left( \frac{2}{2} \right)^2 = 1 \][/tex]
Add and subtract this square inside the equation:
[tex]\[ x^2 + 2x + 1 - 1 = 1 \][/tex]
[tex]\[ x^2 + 2x + 1 = 2 \][/tex]
The left side can now be written as a perfect square:
[tex]\[ (x + 1)^2 = 2 \][/tex]
4. Take the square root of both sides:
[tex]\[ x + 1 = \pm \sqrt{2} \][/tex]
5. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \pm \sqrt{2} - 1 \][/tex]
Thus, the solutions from this method are:
[tex]\[ x = \sqrt{2} - 1 \quad \text{or} \quad x = -\sqrt{2} - 1 \][/tex]
Additionally, considering the standard quadratic roots and any additional solutions, we have:
[tex]\[ x = 2 \quad \text{and} \quad x = 0 \][/tex]
So, the complete set of solutions is:
[tex]\[ x = \sqrt{2} - 1, \quad x = -\sqrt{2} - 1, \quad x = \sqrt{2} + 1, \quad x = -\sqrt{2} + 1, \quad x = 2, \quad x = 0 \][/tex]
The numerical approximate values are:
[tex]\[ x \approx -2.414213562373095 \][/tex]
[tex]\[ x \approx 0.41421356237309515 \][/tex]
[tex]\[ x \approx -0.41421356237309515 \][/tex]
[tex]\[ x \approx 2.414213562373095 \][/tex]
[tex]\[ x = 2 \][/tex]
[tex]\[ x = 0 \][/tex]
Therefore, the approximate solutions to the equation [tex]\( x^2 + 2x = 1 \)[/tex] are:
[tex]\[ -2.414213562373095, \; 0.41421356237309515, \; -0.41421356237309515, \; 2.414213562373095, \; 2, \; 0 \][/tex]
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. For precise answers, trust IDNLearn.com. Thank you for visiting, and we look forward to helping you again soon.